The Changing Marital Union Practices: A New Look on Fertility Behaviour; Experience from Banyankole Families in Sheema Municipality - Kwabaho, Juliet Mujuni; Nyakato, Viola Nilah; Mukasa, Norman (East African Journal of Interdisciplinary Studies, 2023)
The article analyses marital union practices among the Banyankole as part of a study on sociocultural practices and fertility behaviour. The aim was to examine the prevailing reproductive-related cultural practices of the Banyankole and determine their influence on fertility behaviour denoted by choice, spacing and number of children. The qualitative study adapted community-based participatory methods in a grounded theory approach. The study was exploratory in nature based on non-numerical data. Data was collected over 4 months on women and men aged 18 and above living in Sheema Municipality that identify themselves as belonging to the Banyankole ethnic group of Uganda. The study identified major marital union practices existing in the area to include Marriage, Consensual unions, Marital mobility and multi-partnerships. The findings illustrate evolutions in the cultural context of marital union practices and describe their influence on fertility behaviour. The article calls attention to multi-union practices as an important demographic indicator for development practitioners and policymakers in the context of the rapidly advancing sociocultural environment.
Keywords: Marital Practices; Fertility Behaviour; Culture; Marital Mobility; Banyankole